Triacylglycerol Synthesis Enzymes Mediate Lipid Droplet Growth by Relocalizing from the ER to Lipid Droplets - Wilfling, F.; Wang, H.; Haas, J.T.; Krahmer, N.; Gould, T.J.; Uchida, A.; Cheng, J-X.; Cheng, J-X.; Christiano, R.; Fröhlich, F.; Liu, X.; Buhman, K.K.; et al.
Lipid droplets (LDs)store metabolic energy and membrane lipid precursors. With excess metabolic energy, cells synthesize triacylglycerol (TG)and form LDs that grow dramatically. It is unclear how TG synthesis relates to LD formation and growth. Here, we identify two LD subpopulations: smaller LDs of relatively constant size, and LDs that grow larger. The latter population contains isoenzymes for each step of TG synthesis. Glycerol-3-phosphate acyltransferase 4 (GPAT4), which catalyzes the first and rate-limiting step, relocalizes from the endo-plasmic reticulum (ER)to a subset of forming LDs, where it becomes stably associated. ER-to-LD tar-getingof GPAT4 andother LD-localizedTGsynthesis isozymes is required for LD growth. Key features of GPAT4 ER-to-LD targeting and function in LDgrowth are conserved betweenDrosophilaand mammalian cells. Our results explain how TG synthesis is coupled with LD growth and identify two distinct LD subpopulations based on their capacity for local-ized TG synthesis.